The influence of Quercetin on behavior, performance and splenic immunity in broiler chickens - Sara Elsayed El-Kazaz; Mona Hafez Hafez; Ghadeer M. Albadrani; Muath Q. Al-Ghadi; Mohamed M. Abdel-Daim; Yasser Said El-Sayed (Veterinary and Animal Science)
Quercetin (QRT), a potent flavonoid, holds immense mechanistic potential in enhancing various aspects of broiler chicken physiological status. This comprehensive study explores the profound еffеcts of QRT on behavior, productive performance, and immune functions, unraveling the underlying mechanisms behind its efficacy. Four hundred, one-day-old Cobb 500 chicks were placed randomly into 4 supplementation groups (100 birds /group and five replicates) and provided diets enriched with varying concentrations of QRT (0, 200, 400, and 600 ppm) for six weeks. Visual scanning revealed significant (P > 0.05) improvements in feeding and body care behaviors, accompanied by reduced instances of idleness and walking in the QRT-supplemented groups. Moreover, QRT supplementation exerted a substantial (P > 0.05) positive influence on weight gain, feed intake and the final body weight of the broilers. In-depth evaluation of immune parameters, QRT supplementation elicited significant (P > 0.05) enhancements in immune functions, including improved spleen, thymus, and bursa indices, enhanced secretion of immunoglobulin M (IgM) and immunoglobulin A (IgA), and stimulated humoral immunity against sheep red blood cells (SRBCs). Furthermore, QRT displays potent antioxidant properties, as showed by diminished splenic malondialdehyde levels and augmented activity of antioxidative stress enzymes. Remarkably, QRT supplementation elicited dose-dependent upregulation (P < 0.001) of key immune-related genes, such as intеrlеukin-4 (IL-4), interferon-γ (INF-γ), Toll-like receptor 2 (TLR2), and tumor necrosis factor-α (TNF-α) in the splenic tissue. Collectively, these mechanistic insights underscore the profound impact of QRT as a functional feed additive, fostering enhanced behavior, performance, and immune function in broiler chickens, while delivering robust antioxidant fortification.